Persistent fetal vasculature syndrome – clinical image and diagnostic difficulties - Modrzejewska, Monika; Lachowicz, Ewelina; Karczewicz, Danuta; Sawińska, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The aim of this review is to present cases of clinically differentiated picture of persistent fetal vasculature syndrome – PFVS (also called persistent hyperplastic primary vitreous body – PHPVB) observed in group of infants and children. Material and methods: Case records of four children with characteristic changes of posterior form of persistent fetal vasculature syndrome, which were observed on fundus of the eyes, were analyzed retrospectively. Routine ophthalmological examination, genetic, cytogenetic and laboratory tests towards coexisting bacterial, viral and parasitic diseases and congenital anomaly of the eye or chorioretinal neoplastic changes of neonatal period were performed. Ophthalmological changes were archived using Ret-Cam II apparatus (Clarity Medical Systems). Measurement of the axial diameter of the eyes and exclusion coexisting ocular disease by ultrasonography (A-scan US i B-scan US and color Doppler ultrasonography – CDU), were performed. Results: Different clinical image of posterior form of persistent hyperplastic primary vitreous body was observe in ophthalmological examination. Changes such as fibrovascular tissue connecting optic disc (n. II) with ora serrata of the retina coexisting with retinoschisis, retrolental mass or persistent hyaloid artery were observed. Additionally concomitant features in pathological eyes were: iris hypoplasia, corectopia, microphthalmia, congenital cataract, secondary glaucoma, degeneration or retinoschisis and intrvitreous haemorrhage. Strabismus, nystagmus and heart disease in the form of persistent fetal circulation were associated with ophthalmological changes. Inflammatory and genetically determined diseases were excluded in differential diagnosis. Conclusions: The diagnosis of persistent hyperplastic primary vitreous body (PHPVB) was confirmed by characteristic clinical symptoms and results of the additional research. Suggestion of recognition of this syndrome (PHPVB) as well as persistent fetal vasculature syndrome (PFVS) should be implemented diagnostics towards other optic and systemic development defects.